GERAKAN SEMPALAN AGAMA DALAM PERSPEKTIF SEJARAH - Hermanu Joebagio (Millah: Journal of Religious Studies, 2008)
This article tries to analyze separatist groups of Islam in Indonesia. Islamization in Indonesia have been built in the frame of universal values that has close meaning to democration, i.e. hifdz-din, hifdz-nafs, hifdz-nasl, hifdz-mal, and hifdz-aql. Political change took place in 1998 had triggered the emergence of splinters of Islamic religion, they were Salamullah, Isa Bugis, Baha’i, Madi in Palu, Qur’an Suci, and al-Qiyâdah al-Islâmiyah. They used atmosphere of pluralism and inclusivism to form their splinters’ community of religion. In this case, according to historical perspective, Ahmadiyah is different from ather groups. Ahmadiyah has existed before the independence proclamation of Indonesia. They did not accept Muhammad as the last prophet. But, here, there are actually some places to a conversion and reconciliation.